Tradition in Liberation: Women, the Transnational Family, and Caritas in Veritate - Cruz, Gemma Tulud (Feminist theology, 2015)
Caritas in Veritate, the first social encylical of Benedict XVI, tackles the problems of global development and progress towards the common good of all peoples. Taking its cue from the encyclical’s discussion on migration as an ‘aspect of integral human development’ (CV, 62) this article examines the experience of contemporary migrant women and the transnational family vis-à-vis Caritas in Veritate. The paper begins with an overview of Caritas in Veritate followed by a look at the effects of the global economy on women and a discussion on the effects of transnationalism to women and their families, especially with women-away transnational families. The paper then explores the points of convergence and divergence between Caritas in Veritate and the experience of migrant women and the transnational family and ends with a brief conclusion.